O diálogo de abordagens para uma melhor compreensão investigativa - Cappellozza, Alexandre (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
The existence of multiple research paradigms, surrounded by quantitative and qualitative analysis techniques, allows some researchers to adopt their methodological preferences in a dichotomous way, sometimes ignoring other possibilities. However, the fact that there are differences in these research techniques does not prevent the existence of a harmonious dialogue between methods. Thus, the mixed method emerges as a possibility that unites different perspectives of analysis. In this essay, introductory concepts, applications and obstacles towards mixed methods application are presented. The mixed method represents another way to analyze and interpret data under different methodological perspectives and may improve the comprehension of communicational phenomena.